Enhancing rural community empowerment for the realization of independent villages: a strategy for Brangsong sub-district - Suharto Suharto; Hardi Warsono; Tri Yuniningsih; Kushandayani Kushandayani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Advanced and independent village development requires a rural community empowerment budget. The Village Law policy has several implementing regulations, which state that Village Funds are funds sourced from the APBN, and Villages are also allocated in the Regency APBD in the form of Village In fact, it has been almost eight years since the Village Law was implemented and the DD was distributed, there are still most of the villages in Brangsong Sub-district have not yet achieved Independent Villages. This study aims to determine the community empowerment strategy for realizing an Independent Village in Brangsong. The research method is descriptive-qualitative, while the data collection technique uses a documentary study, namely in the form of report data and existing documentation data and analyzed to answer problems in research. Independent villages work. Village community empowerment programmes have a Village Fund management plan. Every movement optimises communal activities, village infrastructure, economic empowerment, and BUM Des (Village Owned Enterprises). in boosting welfare and optimising community social activities related to training local capacity. Thus, Village Human Resources and Natural Resources must be maintained to strengthen the Village community's power, capability, and integrity to achieve an optimum Independent Village.